Integration of education for sustainable development in higher education institution: problems and perspectives - Chaikovska, Hanna (Social work and education, 2023)
The article examines the problem of implementation of education for sustainable development (ESD) at higher education institution (HEI). The research reveals the role of universities in promotion of the principles of sustainable development in the dimension of the Ukrainian education. Emphasis is placed on the preparation of future teachers for the implementation of ESD tasks in their professional activities. It has been established that a modern teacher should master the best skills how to put into practice the sustainable development goals (SDGs), be able to form the sustainable development competencies (SDCs) in students, develop individual and collective responsibility for the sustainable development of society, etc.The issues of the integration of ESD in higher educational institutions at the present stage of the development of higher education have been studied, in particular: the inconsistency of the content of curriculums for the training of future teachers and the current needs of society, the difficulty of providing application of an interdisciplinary approach in the training of students of pedagogical HEIs, the unpreparedness or lack of motivation of teachers to include the SDGs in their teaching, insufficient educational and methodological support, lack of clear criteria for evaluation of students’ learning outcomes and their readiness to perform professional tasks in favour of sustainable development of society, etc.It has been established that overcoming these barriers lies in the area of transformation of the educational environment of HEIs, reorientation of professional education toward preparation of future specialists to the professional activity according to the principles of sustainable development. Significant changes are required in academic and professional curriculums for training future teachers and in the content of pedagogy and training methods for students of pedagogical HEIs, ensuring the availability of teaching aids, manuals and tutorials aimed at ESD. Also the basic set of SDCs should be established for future teachers to achieve sustainable development of society within the framework of their professional responsibility, and the respective indicators should be identified to monitor and evaluate the progress achieved.